Rhodamine isothiocyanate (RITC) as intravital fluorescent marker for programmed cell death. (7th June 2011) - Hristova, M; Thei, L; Picard, M; Peebles, D; Raivich, G
Abstract : The injury-associated cell death is a critical component of neonatal hypoxic ischaemic insult, but its extent normally only becomes visible on postmortem analysis. Here, in vivo availability of fluorescent markers could improve real time assessment of apoptotic processes in the injured but living organism. Although systemic application of rhodamine isothiocyanate (RITC) was initially developed as intravital marker of circulating leucocytes, recent studies in our group showed that the fluorescent marker enters the developing postnatal brain, to label neuronal and glial nuclei, showing blebbing and pyknosis, with a high fraction of RITC+ cells showing costaining for nuclear TUNEL and cytoplasmic cleaved caspase 3. Here, we explored intravital RITC staining to map out dying populations following neonatal hypoxic ischaemic (nHI) insult in mice (Rice-Vannucci), neonatal transection of the mouse facial nerve (nFA) and transection in adult animal (aFA), which is also associated with extensive cell death, but unlike nHI and nFA not associated with TUNEL or Caspase 3 reactivity. In the current study, the neonatal injuries were associated with high numbers of RITC+ cells with a peak at 16 h (nHI) and 24 h (nFA), with a high degree of colocalisation with TUNEL as well as the same temporal profile. In contrast, peak cell death in aFA model at 14 days after injury, was not associated with either RITC or TUNEL reactivity. Altogether, the current data suggest RITC as intravital fluorescent dye that could be used to image the programmed form of cell death and effects of therapeutic intervention in neonatal HI insult.